Improving assessments of the three pillars of Climate Smart Agriculture: Current achievements and ideas for the future - Wijk, Mark T. van; Merbold, Lutz; Hammond, James; Butterbach-Bahl, Klaus (Frontiers Media, 2020)
In this study we evaluate Climate Smart Agriculture (CSA) assessment tools with regard to their suitability for covering not only biophysical but also socio-economic aspects of CSA, focusing on smallholder household level in Low and Middle Income Countries (LMIC). In this opinion piece we give a concise overview of the most recent developments in measuring key indicators and metrics for the three pillars of CSA (food security, adaptation and mitigation) and give our opinion on how we think this would allow for improvements in the current state of assessing CSA in a smallholder farming context. Our assessment shows that all tools reviewed here have a biophysical lens while looking at productivity, and largely ignore potential social (e.g. food security, gender) and economic (poverty) aspects of the sustainability of intensified production. Mitigation was also analyzed in all approaches but few tools go beyond greenhouse gas emissions to analyse environmental sustainability (for example water quality, soil health, ecosystem services) more generically. Climate change adaptation was the CSA pillar with the weakest representation within the approaches reviewed here. Based on an overview of recent advantages in work focusing on CSA our key recommendations are i) to make better use of recent advances in indicator development for sustainability assessments, including work on quantification of water and land footprints in relation to farm management; ii) to use household level analyses to quantify pathways from productivity towards food security and improved nutrition as well as descripting drivers of adoption of adaptation options; and iii) to use recent advances in system specific quantification of greenhouse gas emissions through both LMIC focused modelling and empirical work.